La huella ecológica de la ciudad universitaria Guillermo Falconí Espinosa - Quichimbo Saraguro, Lucía del Cisne (2015)
Nature provides humans with a constant conglomerate of natural resources to meet basic needs. The ecological footprint based its analysis on determining the amount of resources consumed and generated in a given area and their impact on the planet. This research proposed to contribute to improving environmental quality through objectives: Determining the ecological footprint derived from academic and administrative activities of the campus "Guillermo Espinosa Falconí"; and, proposing technical recommendations to optimize the use of resources derived of the ecological footprint. To perform this investigation, information about CO2 emissions were collected from statistical data and direct consumption in three different layers: student, teaching and administrative in the whole study areas (AARNR, AJSA, AEAC). Once these results known, it was lead to literature sources on good environmental practices applicable to the environmental reality and their integration into the university community. The study found a footprint of 530,29 ha/year, corresponding to a per capita ecological footprint of 0,08 ha/year. Finally, guidelines were proposed to help to contribute the sustainability in the use of resources within the study area.